1996
DOI: 10.1016/0165-4608(96)00043-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic hybridization of germ cell tumors of the adult testis: Confirmation of karyotypic findings and identification of a 12p-amplicon

Abstract: Comparative genomic hybridization (CGH) was carried out on 15 primary testicular germ cell tumors (TGCT) o f adolescents and adults and two metastatic residual tumors after chemotherapeu tic treatment. The results were compared with karyotypic data obtained form the same tum or specimens after direct harvesting o f metaphases or short-term in vitro culture. .Both techniques revealed that the m ost consistent abnormality in prim ary TGCT is gain o f 12p-sequences. Although In m o st cases over representation o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
76
0
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 26 publications
9
76
0
3
Order By: Relevance
“…The Figures 3 and 4 illustrate that this frequency is almost identical to that found in testicular 11,34 and mediastinal germ cell tumors of adolescents and adults. 17 In addition, our meta-analysis underlines that CNS-GCTs without 12p gain do not show chromosomal patterns distinct from other germ cell tumors.…”
Section: The Role Of Gain Of 12p In Cns-gctssupporting
confidence: 67%
See 2 more Smart Citations
“…The Figures 3 and 4 illustrate that this frequency is almost identical to that found in testicular 11,34 and mediastinal germ cell tumors of adolescents and adults. 17 In addition, our meta-analysis underlines that CNS-GCTs without 12p gain do not show chromosomal patterns distinct from other germ cell tumors.…”
Section: The Role Of Gain Of 12p In Cns-gctssupporting
confidence: 67%
“…Furthermore, the additional chromosomal imbalances such as gain of 1q or 8 also occur at comparable frequencies as in other gonadal and nongonadal germ cell tumors of adults (Figures 3 and 4). Although CNS-GCTs show no bimodal age distribution as testicular or mediastinal germ cell tumors, 1 our analysis suggests that also in the CNS, germ cell tumors of infancy and early childhood are genetically distinct from those of adolescence and adulthood, as indicated by the analysis of patients 1 and 12, which show profiles characteristic of teratoma and malignant germ cell tumors of Figure 3 Meta-analysis of 116 malignant gonadal and extragonadal GCTs, separated by age and sorted by site 14,17,18,29,34 (including this series and 16 unpublished tumors). Each line represents 100 chromosomal data points of a single tumor, with chromosomal gains illustrated as green bars and losses as red bars, respectively.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…We have recently cloned a novel growth inhibitor and candidate tumour suppressor gene called ING1 using a method that combined PCR-mediated subtractive hybridization of cDNAs (Lisitsyn et al, 1993) from normal and cancerous cells with adaptor-mediated enrichment (Diatchenko et al, 1996) and an in vivo selection assay (Garkavtsev et al, 1996). The ING1 gene localized to chromosome 13q33 ± 34 (Garkavtsev et al, 1997b), a site that has been implicated in the progression of various tumours (Maestro et al, 1996;Motomura et al, 1988;Mostert et al, 1996;YangFeng et al, 1992). It also appears to have a role in programmed cell death as its expression confers sensitivity to apoptosis whereas antisense ING1 protects cells from apoptosis in di erent experimental systems (Helbing et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic, comparative genomic hybridisation (CGH) and allelic imbalance studies of SE and NS have shown that a number of regions in addition to 12p are imbalanced. Reported frequent aberrations common to both SE and NS include gain of material from chromosomes 1, 7, 8, 17, 21 and X and loss of material from chromosomes 4, 5, 11, 13, 18 and Y (van Echten et al, 1995;Korn et al, 1996;Mostert et al, 1996;Sandberg et al, 1996;Summersgill et al, 1998a, b;Kraggerud et al, 2002;von Eyben et al, 2004). In recent years, a number of expression profiling studies have been reported and these have identified overexpressed genes and expression signatures, which distinguish different subtypes of NS (Skotheim et al, 2005).…”
mentioning
confidence: 99%